The Impact of remote and hybrid working on employee engagement and retention of Generation Z - Volokhov, Illia; MacCallum, Tereza; Král, Pavel; Vysoká škola ekonomická v Praze. Fakulta managementu (2025)
This bachelor thesis investigates the impact of remote and hybrid work models on employee engagement and retention, with a focus on Generation Z. Using a theoretical framework and analysis of relevant literature, including the works of Agarwal et al. (2024), Bloom et al., (2024), the study aims to analyse how flexible work arrangements influence employee engagement and retention. Through a combination of quantitative research methods, including surveys with Generation Z employees from XYZ organization, the thesis examines key factors such as engagement and retention. The findings suggest that remote/hybrid work models positively impact engagement and retention. The thesis concludes with practical recommendations for organizations looking to enhance employee satisfaction and retain Generation Z talent in an increasingly remote and hybrid work environment.
Vedoucí práce: Tereza MacCallum
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta managementu
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: management [obor bakal. práce]; bakalářské práce; bachelor's theses